Factors affecting the intention to use financial technology among Vietnamese youth: Research in the time of COVID-19 and beyond - Nguyen Vinh Khuong; Nguyen Thi Thanh Phuong; Nguyen Thanh Liem; Cao Thi Mien Thuy; Tran Hung Son (Economies, 2022)
This study focuses on understanding the factors that affect the intention of using financial technology among young Vietnamese in the context of the COVID-19 pandemic. Fintech studies are abundant in developed countries and mainly focus on consumers' conditions, awareness, habits, and capital. These are expected to differ significantly from the situation in developing countries. We have reviewed factors that can affect the user's intention, including the Perceived Benefit (PB), Perceived Risk (PR), Belief (B), and Social Influence (SI), and rely on the Technology Acceptance Model (TAM) and the Theory of Reasoned Action (TRA) model in this research. The survey sample comprises 161 Z-generation consumers with strong flexibility and knowledge about the use of Fintech. We use the PLS-SEM (partial least squares structural equation modeling) analysis method with the SmartPLS software (SmartPLS GmbH, Oststeinbek, Germany) to evaluate the research model. We find that the Perceived Benefit (PB) has the most significant impact on the intention to use Fintech, followed by Belief (B). However, in general, the factors are not significant, perhaps due to many reasons that are intrinsic in Vietnam. Based on this result, service providers, policymakers, and researchers can calibrate the development and research for the following stages. We offer findings different from the previous research, thus especially extending the literature on young people.
Keywords: 330; COVID-19; financial technology; TAM model; TRA model